From Genes to Treatment: Literature Review and Perspectives on Acid Sphingomyelinase Deficiency in Children - Raluca Maria Vlad; Ruxandra Dobritoiu; Daniela Pacurar (Diagnostics)
Background: Acid sphingomyelinase deficiency (ASMD), most commonly known as Niemann–Pick disease (NPD), is a rare progressive genetic disorder regarding lipid storage. Subtypes A and B are inherited in an autosomal recessive fashion and consist of a genetic defect which affects the sphingomyelin phosphodiesterase 1 gene, leading to residual or lack of enzymatic activity of acid sphingomyelinase (ASM). Materials and Methods: This paper provides a brief history and overview to date of the disease and a comprehensive review of the current literature on ASMD in children, conducted on published papers from the past 10 years. Results: We identified 19 original publications (16 individual case reports and three series of cases—30 patients). The male/female ratio was 1.4. The youngest patient at disease onset was a female newborn with NPD-A. The youngest patient was diagnosed at 4 months. The longest timeframe between onset symptoms and diagnostic moment was 5 years 3 months. A total of nine patients exhibited red cherry macular spots. A total of 13 children exhibited associated lung disease, and four NPD-A patients with pulmonary disease died due to respiratory complications. A total of 11 children exhibited associated growth impairment. Genetic assays were performed in 25 cases (15 homozygous; 9 heterozygous). A total of four children (13.3%) received enzyme replacement therapy (ERT). Therapy outcomes included decreased liver and spleen volumes, improved platelet and leukocytes counts, and body mass index and stature improvement. Conclusions: Sometimes, a small child with a big belly hides a huge dilemma; inherited metabolic disorders are here to challenge clinicians and set the record straight, and genetics is the way of the future in terms of diagnosis and novel treatments. NPD must be considered children with persistent and progressive hepatosplenomegaly and growth failure. Diagnosis requires good clinical skills and access to genetic assays. Since 2022, the FDA has given a green light to a revolutionary enzymatic replacement therapy with human recombinant ASM called Olipudase-alfa. Clinical trial outcomes support its reliability and efficacy in the pediatric population.